1966
DOI: 10.2136/sssaj1966.03615995003000040032x
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Decaying Wood in the Humus Layers of Northern Forests

Abstract: The amount, composition, and persistence of decaying wood in humus layers was examined in yellow birch (Betula alleghaniensis Britton)‐red spruce (Picea rubens Sarg.) stands in the Adirondack Region of New York. The wood is initially attacked by brown rot fungi, but thereafter decomposes very slowly and may persist in the humus layer for a century or more. Separable wood residues weighed as much as 41,800 lb/acre and composed 14 to 30% of the forest floor. These residues were significantly lower in N and P con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 0 publications
1
63
0
Order By: Relevance
“…Although here we are concerned with Douglas-fir, neither decaying wood nor research data are unique to forests of the Pacific Northwest. McFee and Stone (1966) observed that decaying wood persisted for more than 100 years in New York, and Falinski (1978) noted substantial accumulations of coarse woody debris in an old-growth forest in Poland. Appreciable accumulations of fallen trees also occur in the temperate forests of the Andes of central Chile, in the course of long-term forest succession (Veblen 1979).…”
Section: Insect Galleries and Frassmentioning
confidence: 99%
See 1 more Smart Citation
“…Although here we are concerned with Douglas-fir, neither decaying wood nor research data are unique to forests of the Pacific Northwest. McFee and Stone (1966) observed that decaying wood persisted for more than 100 years in New York, and Falinski (1978) noted substantial accumulations of coarse woody debris in an old-growth forest in Poland. Appreciable accumulations of fallen trees also occur in the temperate forests of the Andes of central Chile, in the course of long-term forest succession (Veblen 1979).…”
Section: Insect Galleries and Frassmentioning
confidence: 99%
“…That which has disappeared, however, is not all lost through metabolism of decomposers. Much of it merges into the humus or becomes incorporated into the soil profile (Denny and Goodlett 1956;others 1978, 1979b;McFee and Stone 1966). The importance of internal surface areas is that, through such surfaces, a fallen tree interacts with its environment.…”
mentioning
confidence: 99%
“…Brown rot basidiomycetes cause a highly destructive type of wood decay and are important lignocellulose recyclers in forest ecosystems (7,19,32). During early brown rot, cellulose is rapidly oxidized and depolymerized, even though the porosity of sound wood is too low for enzymes such as cellulases to penetrate (6).…”
mentioning
confidence: 99%
“…The basidiomycetes that cause brown rot of wood are major recyclers of lignocellulose in terrestrial ecosystems and also cause the most destructive type of decay found in wooden structures (7,17,22). Although much remains unknown about their biodegradative mechanisms, there is growing evidence (2,8,11,13,21) that these fungi produce extracellular hydroxyl radicals (…”
mentioning
confidence: 99%